Proteolytic Processing of the Human Immunodeficiency Virus Envelope Glycoprotein Precursor Decreases Conformational Flexibility - Haim, Hillel (American Society for Microbiology, 2013)
The mature envelope glycoprotein (Env) spike on the surface of human immunodeficiency virus type 1 (HIV-1) virions is derived by proteolytic cleavage of a trimeric gp160 glycoprotein precursor. Remarkably, proteolytic processing of the HIV-1 Env precursor results in changes in Env antigenicity that resemble those associated with glutaraldehyde fixation. Apparently, proteolytic processing of the HIV-1 Env precursor decreases conformational flexibility of the Env trimeric complex, differentially affecting the integrity/accessibility of epitopes for neutralizing and nonneutralizing antibodies.